Penerapan Peningkatan Fungsi Lembaga Pengawas Menurut Pemikiran Imam Al Ghazali - Nanda Kurniawan Lubis; Hendra Hendra (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
In this study, the existence of a supervisory system for financial institutions has increased, where initially it was only supervised by a certain line of people, now it has increased, namely with the existence of institutions such as DPS (Sharia Supervisory Board, DSN (National Sharia Council) and so on. Then with the implementation According to Imam Al-Ghazali, the increase in the supervisory function is in accordance with his thoughts regarding hisbah (supervision) or not.                The purpose of this research is to explain the concept of how to increase the function of supervisory institutions according to Imam Al-Ghazali. In the context of increasing the function of supervisory institutions, this will increase public trust in Islamic financial institutions, especially in line with the thoughts of the figure of Imam Al-Ghozali. On the other hand, if the implementation of an increase in the supervisory function is in line with Al Ghazali's thinking, then the operating system of the supervisory institution will work in accordance with Islamic principles.                The method used in this research is qualitative research, which seeks to explore, understand, and seek social phenomena. The research used in this research is qualitative research. Data collection techniques used in this study are through observation (observation), interviews (interviews), and documentation. According to Miles & Huberman, the data analysis technique used consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, drawing conclusions or verification.                The application of increasing the function of supervisory institutions according to Imam Al-Ghazali is by establishing the pillars of hisbah (supervision), including: Muhtasib (hisbah officer), Muhtasab Fih (deeds that are objects of hisbah), Muhtasab'Alaih (perpetrators addressed to hisbah) and Ihtisab (forms of hisbah). The increase in supervisory institutions is in line with the thoughts of the Islamic figure Al Ghazali, which is seen from the DPS (Sharia Supervisory Board) working system which works to ensure Sharia conformity, the DPS supervises, both actively and passively, especially in the implementation DSN fatwa and provide direction/supervision of products/services and business activities so that they comply with Sharia principles.